High Burden of Impetigo and Scabies in a Tropical Country - Steer, Andrew C.; Jenney, Adam W. J.; Kado, Joseph; Batzloff, Michael R.; La Vincente, Sophie; Waqatakirewa, Lepani; Mulholland, E. Kim; Carapetis, Jonathan R. (PLOS Neglected Tropical Diseases, 2009)
Author Summary Scabies and impetigo are often thought of as nuisance diseases, but have the potential to cause a great deal of morbidity and even mortality if infection becomes complicated. Accurate assessments of these diseases are lacking, particularly in tropical developing countries. We performed a series of studies in infants and primary school children in Fiji, a tropical developing country in the South Pacific. Impetigo was very common: more than a quarter of school-aged children and 12% of infants had active impetigo. Scabies was also very common affecting 18% of school children and 14% of infants. The group A streptococcus was the most common infective organism followed by Staphylococcus aureus. The size of the problem has been underestimated, particularly in the Pacific. It is time for more concerted public health efforts in controlling impetigo and scabies.